Polymyxin B‐induced skin hyperpigmentation. Issue 5 (27th May 2020) - Li, Yumeng M.; Milikowski, Clara; Selvaggi, Gennaro; Abbo, Lillian M.; Skiada, Dimitra; Galimberti, Fabrizio
Abstract: Polymyxin B (PMB) is a potent antibiotic targeting gram‐negative bacteria and is associated with serious side effects including nephrotoxicity, neurotoxicity, and hypersensitivity reactions. PMB is a therapeutic option for the management of infections caused by multi‐drug‐resistant (MDR) bacteria and used in combination with other antibiotics when options are limited. We describe the case of a 30‐year‐old female patient with a complex medical history who underwent a multi‐visceral transplantation complicated by intra‐abdominal infections. Subsequently, patient developed diffuse skin darkening after initiation of intravenous PMB for treatment of MDR Pseudomonas aeruginosa . Her skin hyperpigmentation was most prominent on her face and forearms. Hyperpigmentation peaked at around 2 weeks following PMB initiation and was discontinued after 3 weeks when the possibility of PMB hyperpigmentation was raised and other causes were ruled out. Skin biopsy showed hypermelanosis of the basal layer and melanin deposition in the dermis. Overall clinical picture was consistent with PMB‐induced hyperpigmentation. The patient demonstrated some improvement in discoloration within 4 weeks of PMB discontinuation.